2007
DOI: 10.1021/ac0623078
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Electrochemical Sensor Array for On-Line Monitoring of Yeast Fermentations

Abstract: This paper describes the design, modeling, and experimental characterization of an electrochemical sensor array for on-line monitoring of fermentor conditions in both miniaturized cell assays and in industrial scale fermentations. The viable biomass concentration is determined from impedance spectroscopy. As a miniaturized electrode configuration with high cell constant is applied, the spectral conductivity variation is monitored instead of the permittivity variation. The dissolved oxygen concentration is moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Further details about the theoretical aspects, the design, the fabrication, packaging, and experimental characterization of the sensor arrays have been described previously. 22,23 Readout of the sensor array…”
Section: Sensor Array Fabricationmentioning
confidence: 99%
See 3 more Smart Citations
“…Further details about the theoretical aspects, the design, the fabrication, packaging, and experimental characterization of the sensor arrays have been described previously. 22,23 Readout of the sensor array…”
Section: Sensor Array Fabricationmentioning
confidence: 99%
“…The instability of the voltage drop over the salt bridge, including the Nafion junction, was measured to be less than 0.1 mV hr À1 within a 12 h period. Considering the fact that the ideal Nernstian sensitivity for an ISFET is À58.2 mV/pH unit at 20 C, 22 the stability of the voltage drop over the salt bridge was found to be acceptable for the intended application.…”
Section: Salt Bridge Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Krommenhoek et al reported an integrated sensor device with a footprint of < 1 cm 2 to monitor in parallel different parameters in a bioreactor such as the temperature, the pH, the oxygen concentration, and the biomass. 149 Although this device has originally been developed for yeast culture, it could easily be employed in an integrated bioreactor for closely monitoring the growth environment of microtissues.…”
mentioning
confidence: 99%